2020
DOI: 10.1093/mnras/staa3072
|View full text |Cite
|
Sign up to set email alerts
|

On the vanishing orbital X-ray variability of the eclipsing binary millisecond pulsar 47 Tuc W

Abstract: Redback millisecond pulsars (MSPs) typically show pronounced orbital variability in their X-ray emission due to our changing view of the intrabinary shock (IBS) between the pulsar wind and stellar wind from the companion. Some redbacks (“transitional” MSPs) have shown dramatic changes in their multiwavelength properties, indicating a transition from a radio pulsar state to an accretion-powered state. The redback MSP 47 Tuc W showed clear X-ray orbital variability in the Chandra ACIS-S observations in 2002, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…These were folded using PRESTO's prepfold and the ephemeris published by Deneva et al (2016). However, it is well known that many RBs and BWs show a strong orbital variability (Shaifullah et al 2016;Bak Nielsen et al 2020;Hebbar et al 2021), often causing an old ephemeris not to be able to predict the actual orbital phase at a future time. This results in a wrong correction for the orbital Rømer delay (Blandford & Teukolsky 1976) and, consequently, the pulsed emission can be missed when folding.…”
Section: Radio Timing Analysismentioning
confidence: 99%
“…These were folded using PRESTO's prepfold and the ephemeris published by Deneva et al (2016). However, it is well known that many RBs and BWs show a strong orbital variability (Shaifullah et al 2016;Bak Nielsen et al 2020;Hebbar et al 2021), often causing an old ephemeris not to be able to predict the actual orbital phase at a future time. This results in a wrong correction for the orbital Rømer delay (Blandford & Teukolsky 1976) and, consequently, the pulsed emission can be missed when folding.…”
Section: Radio Timing Analysismentioning
confidence: 99%
“…Seq.263 (W29): This source is known as a redback system with a MSP accreting from a main-sequence companion (Edmonds et al 2002). Periodic variation at ∼ 3.19 hr in the optical and X-rays were found by Bogdanov et al (2005), understood as a changing view of the intra-binary shock between the pulsar wind and the stellar wind from its companion, as described in Hebbar et al (2021). The radio counterpart, first detected by Camilo et al (2000) using the Parkes radio telescope, with a pulsating period of 2.35 ms and an orbital period of 3.2 hr, exhibits eclipsing-like behavior in the radio light curve for ∼25% of its orbit.…”
Section: Seq423 (W1)mentioning
confidence: 99%
“…These authors attributed this to a tail of material trailing the pulsar's companion. In the redback 47 Tuc W, Hebbar et al (2021) found that Chandra observations showed that orbital modulation of X-rays was not always present. They suggested that this was due to changes in the system IBS.…”
Section: Implications For 4fgl J17027−5655mentioning
confidence: 99%